PENGEMBANGAN DESAIN PRODUK KRIYA BAMBU DI DESA JAMBUKULON CEPER KLATEN - Pribadi, Syahruna Ricko (ART EDUCARE Pendidikan Seni Rupa, 2013)
Abstract : The objective of the research is to find out (1) the condition of bamboo craft product design produced by the craftsmen in Jambukulon Village of Ceper, Klaten, Central Java (2) the attempts to improve the quality of bamboo craft product design of Jambukulon Village of Ceper, Klaten, Central Java. (3) design development in bamboo craft product design in Jambukulon Village of Ceper, Klaten, Central Java and (4) the manifestation of product resulting from the bamboo craft design development in Jambukulon Village of Ceper, Klaten, Central Java. The type of the research used was a single embedded case study. The data sources are documents, archives, informants, places and events. The data is collected using: in-depth interview, observation, archive document, and focus group discussion. The data validation test is done using triangulation and review informant. The technique of data analysis used was an interactive model. The condition of design produced by the bamboo craf craftsmen in Jambukulon was mebeler product from bamboo stem and animal shaped sculpture souvenir from bamboo hump. The design applied is still consistent with the customer order, only few is their own design, it was because there had not been skill and ability to make design innovation, The attempts to improve the quality of product design included: to change the shape, increase the shape variation, improve the finishing, production techniques, product function responding to the market demand. In addition, design discussion and consulting the design expert, seeing internet reference, newspaper, television, surrounding nature were the other ways to improve the quality of product design, The development of design in bamboo craft product in Jambukulon is done by improving product diversification, by which the development process is conducted through developing several alternative sketches and selecting the design sketch considered as answering the market demand and making it into finished product. The design development is conducted using functional product and souvenir made of bamboo and hump of bamboo.   Keywords: bamboo craft, design development, market, souvenir